(untitled) (Jurnal Bina Praja, 2025)
The recognition of indigenous communities in Indonesia has increasingly been strengthened through regional regulations. Regional Regulation No. 1 of 2019 recognizes the Sebyar indigenous community and positioning tribal chiefs as key actors in the implementation of customary governance. This study aims to analyze the role of the Sebyar Tribal Chief in the implementation of Teluk Bintuni Regional Regulation No. 1 of 2019 concerning the Recognition and Protection of Indigenous Communities and to examine the forms of customary governance that emerged after the regulation, including the supporting and inhibiting factors influencing its implementation. This study employed a descriptive qualitative with a case study design conducted in Tomu Kampong. Data were collected between October and November 2024 through in-depth interview, observation, and documentation studies. The sample consisted of 11 informants, including the Sebyar tribal chief, local government officials, community leaders, and members of the indigenous community. The findings indicate that the Sebyar tribal chief plays a strategic role as a formulator of customary policies, negotiator of customary rights, conflict mediator, and initiator of basic infrastructure development. Following the regional regulation, customary governance underwent a transformation with formal recognition of customary law, enabling the tribal chief to function not only as a customary leader but also as a social mediator, helping restore social harmony through customary rituals and symbols of peace. The regulation’s implementation is supported by customary legitimacy, community support, and cross-actor synergy, but is hampered by limited infrastructure, shifting values among the younger generation, weak administrative capacity, and low corporate commitment to local culture. In conclusion, the success of regional regulations is determined not only by formal regulations, but also by the social legitimacy of tribal chiefs and the socio-cultural conditions of the community. Tribal chiefs are key actors in bridging formal regulations with customary practices who functioned as political-cultural instruments that strengthen customary rights and the sustainability of indigenous communities in Teluk Bintuni.